Audio engineering 101 a beginner's guide to music production - Dittmar, Tim (Focal Press, 2012)
Audio Engineering 101 is a real world guide for starting out in the recording industry. If you have the dream, the ideas, the music and the creativity but don't know where to start, then this book is for you! Filled with practical advice on how to navigate the recording world, from an author with first-hand, real-life experience, Audio Engineering 101 will help you succeed in the exciting, but tough and confusing, music industry. Covering all you need to know about the recording process, from the characteristics of sound to a guide to microphones to analog versus digital recording. Dittmar covers all the basics- equipment, studio acoustics, the principals of EQ/ compression, music examples to work from and when and how to use compression. FAQ's from professionals give you real insight into the reality of life on the industry. * Easy to understand. A real beginner's music production guide. No experience needed! * Covers aspects of audio often overlooked: internships, people skills, jobs, and the art side * Geared towards anyone wanting to do Music Production either as a hobby or potential career path *Gives you insight into the process of music production by unraveling the mystery behind producing records.
Includes bibliographical references and index. - Print version record
Keywords: Sound -- Handbooks, manuals, etc -- Recording and reproducing; Sound -- Handbooks, manuals, etc -- Recording and reproducing -- Digital techniques; Son; Enregistrement et reproduction; Guides, manuels, etc; Technology; Sound; Recording and reproducing; Sound; Recording and reproducing; Digital techniques; manuals (instructional materials); handbooks; Handbooks and manuals; Guides et manuels